Undergraduate Students’ Difficulties in Solving Derivative and Integral Mathematical Problems (Sains Humanika, 2019)
Undergraduate students often experienced difficulty in solving problem related to derivative and integral topics. The main goal of this study was to investigate the reasons of students’ difficulties in solving derivative and integral problems based on mathematical thinking approach. The participants of the study consisted of 63 undergraduate students. A test contained derivative and integral problems was given to students and the results was analyzed by quantitative and qualitative methods. Results revealed that the reasons of students’ difficulties in solving problems were inability to use suitable problem solving framework, weakness in recalling previous knowledge in entry and attack steps of specialization and generalization, weakness in making connection between embodied and symbolic worlds of mathematical thinking and using symbolic world rather than embodied world.
Keywords: Derivative; difficulties; mathematical thinking; problem solving; integral; undergraduate